Impaired Visual Motor Coordination in Obese Adults - David Gaul; Arimin Mat; Donal O’Shea; Johann Issartel (Journal of Obesity)
Objective. To investigate whether obesity alters the sensory motor integration process and movement outcome during a visual rhythmic coordination task. Methods. 88 participants (44 obese and 44 matched control) sat on a chair equipped with a wrist pendulum oscillating in the sagittal plane. The task was to swing the pendulum in synchrony with a moving visual stimulus displayed on a screen. Results. Obese participants demonstrated significantly (p<0.01) higher values for continuous relative phase (CRP) indicating poorer level of coordination, increased movement variability (p<0.05), and a larger amplitude (p<0.05) than their healthy weight counterparts. Conclusion. These results highlight the existence of visual sensory integration deficiencies for obese participants. The obese group have greater difficulty in synchronizing their movement with a visual stimulus. Considering that visual motor coordination is an essential component of many activities of daily living, any impairment could significantly affect quality of life.